2017
DOI: 10.1177/0021998317692398
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting carbon nanotube fillers towards enhancement of thermal conductivity in polymer nanocomposites: A review

Abstract: Thermally conductive polymer composites have opened up new possibilities in various applications including solar cells, power generators, electronics, biomedical applications, etc. Polymer matrices have some interesting advantages to offer such as being lightweight, cost effective, corrosion resistant, and many more. However, the thermal conductivity of a polymer matrix is relatively low for some commercial applications. Recent research has focused on enhancing the thermal conductivity of polymer composites th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…CNTs with a thermal conductivity an average of 10-fold lower than metals/ceramics have shown great success as good thermal insulators [ 90 ]. Furthermore, additional physical characteristics in terms of their light weight, cost-effectiveness, and corrosion resistance are very importance in the future trend of nanocomposite technology [ 176 ]. Interestingly, these characteristics can be envisioned as new possibilities for various applications of their thermal properties such as thermal interface materials, heat sinks, printed circuit boards, connectors, and other high-performance thermal management systems [ 90 ].…”
Section: Performance Of Carbon Nanotube–polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…CNTs with a thermal conductivity an average of 10-fold lower than metals/ceramics have shown great success as good thermal insulators [ 90 ]. Furthermore, additional physical characteristics in terms of their light weight, cost-effectiveness, and corrosion resistance are very importance in the future trend of nanocomposite technology [ 176 ]. Interestingly, these characteristics can be envisioned as new possibilities for various applications of their thermal properties such as thermal interface materials, heat sinks, printed circuit boards, connectors, and other high-performance thermal management systems [ 90 ].…”
Section: Performance Of Carbon Nanotube–polymer Compositesmentioning
confidence: 99%
“…Markers for the prediction of higher thermal conductivity based on polymer morphology have been widely investigated, and it has been shown that more defects at the crystalline structures, the lower the intrinsic thermal conductivity of the crystal. This leads to phonon scattering, which is known to shorten the mean free path that finally reduced the thermal conductivity [ 176 ]. The morphology of CNT reinforced polymer composites significantly affect thermal properties.…”
Section: Performance Of Carbon Nanotube–polymer Compositesmentioning
confidence: 99%
“…395,396 Consequently, it has become a major issue how to benet from the optimization of the interface through the chemical functionalization of carbon nanotubes without any noticeable loss of the intrinsic thermal properties of the ller. While great achievements have been made in this eld, 397,398 how to maximize the benets derived from the intrinsic thermal properties of carbon nanotubes for polymer nanocomposite materials is still a major challenge.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Many researchers have reported the benecial advantages of adding CNTs to polymeric membranes. These include increased hydrophilicity and oleophobicity, 35 improved thermal, 36 electrical, 37 and mechanical 3 properties of the composite membranes. CNTs as nanoller in polymer matrix have attracted a great deal of attention because of their high specic surface area, easy functionalization, chemical stability and proper compatibility.…”
Section: Carbon Nanotubesmentioning
confidence: 99%